Synthesis, characterization, photophysical, and photochemical properties of novel phthalocyanines containing thymoxy groups as bioactive units - ODABAŞ, ZAFER (My University, 2023)
In this study, new 4-chloro-5-(2-isopropyl-5-methylphenoxy)phthalonitrile compound, containing bioactive thymoxy group, and its metal-free phthalocyanine and metallo-phthalocyanine derivatives were synthesized for the first time. Their structures were determined by spectroscopic methods such as FTIR, UV–Vis, 1H-, and 13C-NMR (for phthalonitrile derivative), MALDI-TOF mass spectrometry (for phthalocyanine derivatives) and elemental analysis as well. The phthalocyanines showed excellent solubility in polar and nonpolar solvents without aggregation and absorb at long wavelengths with their high molar coefficient. In N,N-dimethylformamide, the effects of the type of central metal ions [metal-free, indium(III) acetate, lutetium(III) acetate, magnesium(II) or zinc(II)] in the phthalocyanine, containing bioactive thymoxy group, cavity on the spectroscopic, photophysical, and photochemical properties of the phthalocyanines were determined. These features are compared with each other. Lutetium(III) acetate phthalocyanine did not show any fluorescence, while metal-free phthalocyanine and indium(III) acetate phthalocyanine showed low fluorescence. It was determined that magnesium phthalocyanine significantly enriched the fluorescence, and zinc phthalocyanine had appropriate and sufficient fluorescence. Lutetium(III) acetate and zinc(II), especially indium(III) acetate phthalocyanines, could produce large amounts of singlet oxygen. Metal-free and magnesium phthalocyanines had the capacity to produce sufficient singlet oxygen (it means production of enough amount of singlet oxygen by a photosensitizer candidate during PDT applications). All phthalocyanines have sufficient and suitable photostability (it means an ideal photosensitizer should be stable under light irradiation until complete its PDT activation, and it should be decomposed after its PDT activation so that it does not accumulate in the body). With these determined properties, magnesium(II), especially indium(III) acetate and zinc(II) phthalocyanines, may be suitable candidates as type II photosensitizers for photodynamic therapy applications. Lutetium(III) acetate phthalocyanine may be a photosensitizer candidate in photocatalytic applications.
Keywords: Kimya; İnorganik Kimya; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Inorganic Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; KİMYA, İNORGANİK VE NÜKLEER; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; CHEMISTRY, INORGANIC & NUCLEAR; MATERIALS SCIENCE, MULTIDISCIPLINARY; Metaller ve Alaşımlar; Fizik Bilimleri; İnorganik kimya; Malzeme Kimyası; Metals and Alloys; Physical Sciences; Materials Chemistry